Conceptual framework of sustainable corporate entrepreneurship - Serai, M.H. (Institute of Electrical and Electronics Engineers Inc., 2015)
Recently corporate entrepreneurship (CE) is getting considerable attention amongst researchers, especially in the developed economies. Looking at the significance of CE, research communities from the developing countries are also paying substantial attention towards corporate entrepreneurship. The literature has evolved from entrepreneurship to corporate entrepreneurship and is now moving towards sustainable corporate entrepreneurship. Initially, it was considered that corporate entrepreneurship had three main dimensions, such as innovativeness, proactiveness and risk taking. Later, competitive aggressiveness and autonomy were also introduced as corporate entrepreneurship dimensions. It has been observed that these dimensions play an important role in the economic growth for large businesses. Similarly, sustainability has also been getting attention, after it had been emphasised in modern literature and by various international organisations. Sustainability covers social, environmental and economic issues, thus recommending the importance of both corporate entrepreneurship and sustainability. This study aims to propose a framework of sustainable corporate entrepreneurship and firm performance for Malaysian public listed firms. This proposed framework can be generalised to apply to other countries. Sustainability has been incorporated with corporate entrepreneurship. In order to measure the entrepreneurial activities, this framework proposes firm performance as a dependent variable for a sustainable corporate entrepreneurship framework. Â© 2015 IEEE.